v-rel induces expression of three avian immunoregulatory surface receptors more efficiently than c-rel. - Hrdlicková, R (1994)
The c-rel gene is a member of NF-kappa B/rel family of transcription factors that regulate expression of a variety of immunoregulatory molecules. The viral oncogene, v-rel, is a truncated and mutated form of the turkey c-rel gene expressed by reticuloendotheliosis virus, strain T. In this study, we demonstrated that three avian immunoregulatory receptors, major histocompatibility (MHC) antigens class I and class II as well as the interleukin-2 receptor (IL-2R), were induced on the surface of splenic tumor cells isolated from chickens infected with reticuloendotheliosis virus, strain T. All cell lines derived from splenic tumors expressed these three proteins. Their expression also correlated with the appearance of endogenous c-rel during a graft-versus-host reaction. In vitro, both c-rel and v-rel induced MHC class I, MHC class II, and IL-2R on an avian B-lymphoid cell line, DT95, and a T-lymphoid cell line, MSB-1. Quantitative kinetic analysis demonstrated both the accumulation of MHC class II mRNA and the appearance of surface MHC class II protein in response to the synthesis of either v-rel or c-rel. We show that v-rel induced the expression of MHC class II in the avian B-cell lines DT40 and DT95 more rapidly than c-rel and that, several weeks after infection, v-rel induced MHC class II as much as 50-fold more efficiently than c-rel. Finally, in vitro infection of splenocytes with retroviruses that express v-rel or c-rel induced MHC class I, MHC class II, and IL-2R expression. Quantitative analysis confirmed that p59v-rel was consistently more efficient at inducing expression of all three immunoregulatory receptors than exogenous p68c-rel. These data suggest that during tumor development, v-rel functions to induce (or suppress) the expression of genes similarly induced (or suppressed) by c-rel. The observations reported in this study are not in agreement with a model in which v-rel promotes tumor development by functioning as a dominant negative mutant of c-rel. In contrast, these findings support the hypothesis that lymphocyte immortalization and tumor development are the result, at least in part, of the capacity of v-rel to function as a dominant positive mutant that induces expression of genes normally regulated by c-rel.